Quantitative Study of Abdominal Blood Flow Patterns in Patients with Aortic Dissection by 4-Dimensional Flow MRI - Liu, D.; Fan, Z.; Li, Y.; Zhang, N.; Sun, Zhonghua; An, J.; Stalder, A.; Greiser, A.; Liu, J. (Nature Publishing Group, 2018)
The purpose of this study is to evaluate the hemodynamic characteristics of the true lumen (TL) and the false lumen (FL) in 16 patients with aortic dissection (AD) using 4D flow magnetic resonance imaging (MRI) and thoracic and abdominal computed tomography (CT) angiography. The quantitative parameters that were measured in the TL and FL included velocity and flow. The mean area and regurgitant fraction of the TL were significantly lesser at all four levels (p < 0.05); the average through-plane velocity, peak velocity magnitude, average net flow, peak flow, and net forward volume in the TL were considerably higher (p < 0.05). The intimal entry's size was negatively correlated with the blood flow velocity and flow rate in the TL (p < 0.05) and positively correlated with the average through-plane velocity, average net flow, and peak flow in the FL (p < 0.05); the blood flow indices in the TL were enhanced with an increase in the intimal entry numbers (p < 0.05) and the peak flow in the FL was lowered (p = 0.025); if FL thrombosis existed, the average through-plane velocity and peak velocity magnitude in the TL were substantially higher (p < 0.05). 4D flow MRI facilitates qualitative and quantitative analysis of the alterations in the abdominal aortic blood flow patterns.